2020
DOI: 10.1021/acs.langmuir.0c01104
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Pore Size and Connectivity of Alumina-Particle-Stabilized Foams Using Sodium Dodecyl Sulfate: Role of Surfactant Concentration

Abstract: Herein, alumina foams were prepared from particle-stabilized foams, fabricated by direct foaming methods, that varied according to the concentration of sodium dodecyl sulfate (SDS). To confirm the formation mechanism of pore structures in alumina ceramic foams with varying SDS concentrations, the adsorption density, contact angle, ζ-potential, and surface tension of the alumina particles dispersed in SDS were analyzed. Additionally, model analysis was performed to confirm the interaction between alumina and ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Khan et al synthesized Ag NPs in the presence of CTAB using Raphanus sativus extract . Although various studies have been reported using plant extracts and surfactants, most of the times their individual effects have been reported. ,, Therefore, while using flower extract as a reducing agent, it was imperative to study the effect of anionic surfactants on the formation and structural features of Ag NPs . Hitherto, a relationship is developed between the effects of the anionic surfactant [SDS] and Cassia siamea flower petal extract ([CSFE]) by studying their mutual effects on the synthesis and overall texture development of Ag NPs.…”
Section: Introductionmentioning
confidence: 99%
“…Khan et al synthesized Ag NPs in the presence of CTAB using Raphanus sativus extract . Although various studies have been reported using plant extracts and surfactants, most of the times their individual effects have been reported. ,, Therefore, while using flower extract as a reducing agent, it was imperative to study the effect of anionic surfactants on the formation and structural features of Ag NPs . Hitherto, a relationship is developed between the effects of the anionic surfactant [SDS] and Cassia siamea flower petal extract ([CSFE]) by studying their mutual effects on the synthesis and overall texture development of Ag NPs.…”
Section: Introductionmentioning
confidence: 99%
“…Recovery is the percentage of the total mineral or metal contained in the ore, which is recovered in the concentrate. The recovery of the concentrate is given by this Equation [18,31]: The zeta potential measurements were carried out using a zeta potential analyzer (ELS-Z Zeta Potential analyzer, Otsuka Electronics, Osaka, Japan). For measurement, the samples were ground to particles less than 5 µm using an agate mortar.…”
Section: Experimental Methods and Analysismentioning
confidence: 99%
“…Recovery is the percentage of the total mineral or metal contained in the ore, which is recovered in the concentrate. The recovery of the concentrate is given by this Equation [18,31]:…”
Section: Experimental Methods and Analysismentioning
confidence: 99%
“…Herein, we have developed fast-curing GP foam derived by the gaseous method, followed by analysis on porosity, compressive strength, and thermal conductivity. Herein, the effect of the contents of a foaming agent (hydrogen peroxide, H 2 O 2 ) and a surfactant (Sodium dodecyl sulfate (SDS), NaC 12 H 25 SO 4 ) was conducted [31].…”
Section: Introductionmentioning
confidence: 99%